2019
DOI: 10.1111/jphp.13159
|View full text |Cite
|
Sign up to set email alerts
|

TNBG-5602, a novel derivative of quinoxaline, inhibits liver cancer growth via upregulating peroxisome proliferator-activated receptor γ in vitro and in vivo

Abstract: Objectives TNBG‐5602 is a newly synthesized compound with an isoquinoline structure. In the present study, we demonstrated the anticancer effect of TNBG‐5602 in in‐vitro and in‐vivo models and investigated its possible anticancer mechanism. Methods The antiproliferation effect of TNBG‐5602 in vitro was evaluated in human liver cancer cell line QGY‐7701. The acute toxicity of TNBG‐5602 was evaluated in mice. The anticancer activity of TNBG‐5602 in vivo was assessed in a xenograft model of human liver cancer cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 40 publications
(77 reference statements)
0
10
0
Order By: Relevance
“…Introducing hydrophilic substituents into a core ring is a conventional and effective method for increasing the water solubility of lead compounds, which has been widely used in the process of discovering candidates. , For example, irinotecan, benotican, and topotecan were obtained by introducing dimethylamino, isopropylamino, and 1,4′-bipiperidine groups at the 7, 9, or 10 positions of camptothecin, respectively, and they all showed a dramatic increase in water solubility compared to that of the lead compound . Based on the same design strategy, modification of TNBG by incorporating a flexible linker bearing an N , N -dimethyl moiety into the nucleus led to the discovery of TNBG-5602 (Figure ), which demonstrated enhanced antiproliferative activity and water solubility compared to TNBG . , Encouraged by this positive outcome, a series of hydrophilic linkers containing hydroxyl groups, carboxyl groups, morpholine, piperidine, and piperazine with different carbon lengths were introduced into the A, C, or E rings of TNBG with the aim of further improving the antitumor activity and water solubility of TNBG-5602 in this study. Moreover, different substituents, including electron-donating or electron-withdrawing groups, were introduced to the A and E rings to systemically investigate the structure–activity relationship (SAR) and pharmacodynamic properties.…”
Section: Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Introducing hydrophilic substituents into a core ring is a conventional and effective method for increasing the water solubility of lead compounds, which has been widely used in the process of discovering candidates. , For example, irinotecan, benotican, and topotecan were obtained by introducing dimethylamino, isopropylamino, and 1,4′-bipiperidine groups at the 7, 9, or 10 positions of camptothecin, respectively, and they all showed a dramatic increase in water solubility compared to that of the lead compound . Based on the same design strategy, modification of TNBG by incorporating a flexible linker bearing an N , N -dimethyl moiety into the nucleus led to the discovery of TNBG-5602 (Figure ), which demonstrated enhanced antiproliferative activity and water solubility compared to TNBG . , Encouraged by this positive outcome, a series of hydrophilic linkers containing hydroxyl groups, carboxyl groups, morpholine, piperidine, and piperazine with different carbon lengths were introduced into the A, C, or E rings of TNBG with the aim of further improving the antitumor activity and water solubility of TNBG-5602 in this study. Moreover, different substituents, including electron-donating or electron-withdrawing groups, were introduced to the A and E rings to systemically investigate the structure–activity relationship (SAR) and pharmacodynamic properties.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Our previous data demonstrated that TNBG and its analogue TNBG-5602 could induce lipid accumulation in cancer cells. Therefore, A549 and HepG2 cells were treated with 14g and stained with Oil Red O to examine its effect on lipid accumulation. As shown in Figure , red lipid droplet accumulation in the cytoplasm of cancer cells was observed after treatment with 14g , which was in line with that of TNBG-5602 , as evidenced by Oil Red O staining of the cellular lipid.…”
Section: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tetrazanbigen is a novel scaffold bearing quinoxaline core with anticancer activity in vitro and in vivo, which was firstly reported by our team [5]. In order to improve the physical properties and biological activities, many efforts were made and a series of tetrazanbigen derivatives were designed and synthesized [6,7]. In this study, the crystal structure of title compound is reported for the first time.…”
Section: Commentmentioning
confidence: 99%